Cation disorder and phase transitions in the structurally complex solar cell material Cu2ZnSnS4. Issue 32 (26th July 2017) - Bosson, C. J.; Birch, M. T.; Halliday, D. P.; Knight, K. S.; Gibbs, A. S.; Hatton, P. D.
Abstract : The highest-resolution neutron scattering yet reported is used to examine disorder, and the order–disorder transition temperature is found to depend on elemental composition. Abstract : Cu2 ZnSnS4 (CZTS) is a technologically important and complex quaternary semiconductor and a highly promising material for the absorber layer in sustainable thin film solar cells. Its photovoltaic performance is currently limited by low open-circuit voltage, thought to be due to a range of point defects such as disorder between the copper and zinc lattice sites. This is the highest-resolution neutron diffraction study reported for CZTS, which unambiguously identifies the crystal symmetry and accurately quantifies precise values for the disorder on all cation symmetry sites as a function of temperature. Two samples of CZTS were fabricated by solid state reaction and their compositions were measured by inductively-coupled plasma mass spectroscopy, which identified significant tin loss during growth, leaving the samples Sn-poor, Cu-rich and Sn-poor, Zn-rich respectively. Both samples were found exclusively to adopt the tetragonal kesterite crystal structure with significant cation disorder, which is investigated in detail over the range 4–1275 K. Importantly, and in contrast to previous reports, the 2 a Wyckoff site shows disorder equal to or greater than the 2 c site. The order–disorder phase transition was observed at different temperatures for the two compositions, 489 and 501 K respectively, lower than previously reported. The kesterite–sphalerite transition was observed between 1250 and 1275 K for the Sn-poor, Cu-rich sample, significantly higher than previously reported. These results provide new insights into the high levels of disorder present in CZTS and confirm that composition and cation disorder have a significant effect on the phase transition mechanism. This work will enable the development of routes to the fabrication of higher-efficiency photovoltaic devices.